Prevalence and diversity of IncX plasmids carrying fluoroquinolone and β-lactam resistance genes in Escherichia coli originating from diverse sources and geographical areas - Dobiasova, Hana; Dolejská, Monika (Journal of antimicrobial chemotherapy, 2016)
OBJECTIVES: To describe the prevalence and diversity of IncX plasmids with antibiotic resistance genes in Enterobacteriaceae and to identify the most disseminated lineages of the plasmid family. METHODS: IncX plasmids were screened in 1894 Enterobacteriaceae isolates resistant to cefotaxime (2 mg/L) or with reduced susceptibility to ciprofloxacin (0.05 mg/L) obtained from various sources in five continents using PCR. IncX plasmid-harbouring isolates were identified using MALDI-TOF or biochemical tests, and screened for antibiotic resistance genes using PCR and sequencing; their clonality was determined by PFGE. Horizontal transfer of plasmids was tested using transformation and conjugation. IncX plasmids were characterized by S1-nuclease and PFGE, RFLP and hybridization. RESULTS: A total of 164 Escherichia coli isolates (8.7%, n = 1894) carried at least one IncX subgroup. Seven isolates harboured two distinct subgroups. IncX1 subgroup was found in 93 isolates, followed by IncX2 (35 isolates), IncX4 (28) and IncX3 (15). IncX4 plasmids were not transferred horizontally as single plasmids and therefore excluded from further analysis. The most disseminated lineages of IncX plasmids included IncX1 harbouring qnrS1 and blaTEM-1,-135 found in 36 E. coli from different sources in Europe and Australia and IncX2 carrying qnrS1 and tet(A) detected in nine E. coli from wildlife in Europe. IncX3 plasmids harboured predominantly blaSHV-12 and qnrS1 or qnrB7. CONCLUSIONS: IncX plasmids were widely distributed in E. coli from wildlife in Europe and were predominantly associated with fluoroquinolone resistance genes. Plasmids showing indistinguishable restriction profiles were identified in E. coli from different sources and countries suggesting wide dissemination of certain plasmid lineages.
Keywords: Animals; přenos genů horizontální; pulzní gelová elektroforéza; Molecular Typing; Genotype; Escherichia coli Infections; infekce vyvolané Escherichia coli; Prevalence; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Escherichia coli; polymerázová řetězová reakce; Conjugation, Genetic; Polymerase Chain Reaction; bakteriální geny; Global Health; Transformation, Bacterial; celosvětové zdraví; divoká zvířata; shluková analýza; lidé; genotyp; molekulární typizace; Fluoroquinolones; fluorochinolony; Electrophoresis, Gel, Pulsed-Field; bakteriální léková rezistence; Gene Transfer, Horizontal; Genetic Variation; konjugace genetická; prevalence; beta-laktamy; plazmidy; Animals, Wild; beta-Lactams; Sequence Analysis, DNA; bakteriální transformace; Genes, Bacterial; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Plasmids; zvířata; sekvenční analýza DNA; Cluster Analysis; Drug Resistance, Bacterial; genetická variace; Humans